The Conflict Potential of Students in a Polyethnic Region - I L Pozdeev (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2012)
On the basis of sociological research the article examines various forms of social activity of students in a poly-ethnic region, including their participation in the protest movement. The author notes that the students mainly choose legal forms of protecting their interests. Among the young people, the level of tolerance as regards the representatives of other cultures, is quite high, which in many respects results from the centuries-old experience of inter-ethnic coexistence, accumulated in the regional community.